2015
DOI: 10.1111/jfbc.12179
|View full text |Cite
|
Sign up to set email alerts
|

DNA Protection and Antioxidant Potential of Chestnut Shell Extracts

Abstract: Castanea crenata is a species of chestnut originally native to South Korea and Japan. In this study, chestnut shell was investigated as a potential source of antioxidant compounds. Distilled water and ethanol extracts were prepared from chestnut shell and their antioxidant activities were investigated in vitro using different analytical methods, including 2,2‐diphenyl‐1‐picrylhydrazyl, 2,2‐azino‐bis‐(3‐ethylbenzothiazoline‐6‐sulfonic acid), hydroxyl, superoxide radical and nitrite scavenging, reducing (Fe3+ to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The extract showed high phenolic content which justified the antioxidant and DNA damage inhibition properties of the plant. This result agreed with the results of many other studies suggested that phenolic compounds can protect the DNA from the oxidative damage [28][29][30][31]. The DNA damage inhibition potential of the extract could be used in cancer prevention.…”
Section: Dna Damage Inhibition Efficiencysupporting
confidence: 91%
“…The extract showed high phenolic content which justified the antioxidant and DNA damage inhibition properties of the plant. This result agreed with the results of many other studies suggested that phenolic compounds can protect the DNA from the oxidative damage [28][29][30][31]. The DNA damage inhibition potential of the extract could be used in cancer prevention.…”
Section: Dna Damage Inhibition Efficiencysupporting
confidence: 91%
“…It has been demonstrated that chestnut is also rich in vitamin E and carotenoids [2,4]. In addition, chestnut fruit has long been considered beneficial to the functions for human as Chinese traditional medicine in "Compendium of Materia Medica" [5], and it has also been used as cosmetic supplement in Korea peninsula [6].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese chestnut ( Castanea mollissima Blume) is a native species in mainland China with a cultivation history of over 3000 years [ 1 ]. Chestnut has long been used as a kind of cosmetic supplement in Korea [ 2 ]. Moreover, chestnuts are a healthy food resource with high nutritional values, containing high levels of carbohydrates and proteins but zero cholesterol and gluten [ 3 ].…”
Section: Introductionmentioning
confidence: 99%